2021
DOI: 10.1159/000519068
|View full text |Cite
|
Sign up to set email alerts
|

Time in Neurogenesis: Conservation of the Developmental Formation of the Cerebellar Circuitry

Abstract: The cerebellum is a conserved structure of vertebrate brains that develops at the most anterior region of the alar rhombencephalon. All vertebrates display a cerebellum, making it one of the most highly conserved structures of the brain. Although it greatly varies at the morphological level, several lines of research point to strong conservation of its internal neural circuitry. To test the conservation of the cerebellar circuit, we compared the developmental history of the neurons comprising this circuit in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4
2

Relationship

4
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 55 publications
3
9
0
Order By: Relevance
“…Our analyses of the developing cerebellum support early spatiotemporal patterning of Purkinje and granule cell subtypes that contributes to the cellular organization in the adult. We found consensus subtypes for most neural cell types in the developing cerebellum and observed equivalent sequences and timings of cell type emergence in the three species, in line with the previously proposed conservation of the cerebellum's cellular architecture and developmental program across amniotes 4,50 . A notable exception is the significantly higher relative abundance of Purkinje cells during early fetal development in human.…”
Section: Discussionsupporting
confidence: 88%
“…Our analyses of the developing cerebellum support early spatiotemporal patterning of Purkinje and granule cell subtypes that contributes to the cellular organization in the adult. We found consensus subtypes for most neural cell types in the developing cerebellum and observed equivalent sequences and timings of cell type emergence in the three species, in line with the previously proposed conservation of the cerebellum's cellular architecture and developmental program across amniotes 4,50 . A notable exception is the significantly higher relative abundance of Purkinje cells during early fetal development in human.…”
Section: Discussionsupporting
confidence: 88%
“…This confirmed that the pulse-labeling was effective, as there was no remaining EdU mark in the progenitor cells days after the injection [ Fig. 2D-F , (Rueda-Alaña and García-Moreno, 2022)].…”
Section: Resultssupporting
confidence: 64%
“…In part, the rule of the older gets richer suggests that ancient circuits -such as those in brainstem, related to autonomic animal functions and directly involved in the survival of the animal- are more influential in the network and more stable in evolution. As a crucial example, it has been recently demonstrated the deeply conserved neurogenic formation of the cerebellum in several species of vertebrates 43 , and its remarkable orchestrating hub role to impact epileptic brain dynamics 35 . On the other side of the spectrum, circuits related to associative tasks -more related to cognition and human-specific behaviour- are not necessarily conserved, appear later in neurogenesis.…”
Section: Discussionmentioning
confidence: 99%